Utility of pharmacogenetic testing to optimise antidepressant pharmacotherapy in youth: a narrative literature review - Roberts, Bradley; Cooper, Zahra; Lu, Stephanie; Stanley, Susanne; Majda, Bernadette T.; Collins, Khan R. L.; Gilkes, Lucy; Rodger, Jennifer; Akkari, P. Anthony; Hood, Sean D. (Frontiers in Pharmacology, 2023)
Pharmacogenetics (PGx) is the study and application of how interindividual differences in our genomes can influence drug responses. By evaluating individuals' genetic variability in genes related to drug metabolism, PGx testing has the capabilities to individualise primary care and build a safer drug prescription model than the current 'one-size-fits-all' approach. In particular, the use of PGx testing in psychiatry has shown promising evidence in improving drug efficacy as well as reducing toxicity and adverse drug reactions. Despite randomised controlled trials demonstrating an evidence This is a provisional file, not the final typeset article base for its use, there are still numerous barriers impeding its implementation. This review paper will discuss the management of mental health conditions with PGx-guided treatment with a strong focus on youth mental illness. PGx testing in clinical practice, the concerns for its implementation in youth psychiatry, and some of the barriers inhibiting its integration in clinical healthcare will also be discussed. Overall, this paper provides a comprehensive review of the current state of knowledge and application for PGx in psychiatry and summarises the capabilities of genetic information to personalising medicine for the treatment of mental ill-health in youth.